Avaliação clínica de pacientes submetidos à colocação de implantes zigomáticos pela técnica de Stella & Warner - Araújo, Pryscyla Pascally Targino (2012)
This study aimed to evaluate patients who underwent placement of zygomatic implants technique by Stella & Warner, considering the survival of conventional and zygomatic implants, sinus health and level of patient satisfaction in relation to oral rehabilitation. We evaluated 28 patients where 14 had received conventional and zygomatic implants, being rehabilitated with implant-fixed dentures (group 1) and 14 were rehabilitated only with conventional implants and implant-fixed dentures (group 2). The study had four phases, represented by radiographic evaluation of implants (stage I), clinical evaluation (stage II), assessing the health of the maxillary sinus (stage III) and a questionnaire to measure satisfaction of rehabilitation with fixed prosthesis implant Total -backed (stage IV). Group 2 underwent only stage IV, while group 1 participated in all stages. Descriptive analysis and statistics were performed, using the t test for independent samples in the evaluation of phase IV. The results demonstrated that the technique of Stella & Warner proved effective, allowing a high survival rate of conventional implants and zygomatic (100%), considering a minimum follow-up of 15 months and maximum 53 months after prosthetic rehabilitation. There were no pathological changes in tissues periimplants conventional and zygomatic implants analyzed. Radiographic findings showed satisfactory levels bone implants in the oral rehabilitation with conventional zygomatic implants and a good positioning of the apex of the zygomatic implants over the zygomatic bone. The presence of the zygomatic implant did not cause sinus and the t test showed a satisfaction index lower in group 1 compared with group 2. The zygomatic implant placement technique by Stella & Warner proved to be a predictable technique with high survival rate in patients with atrophic jaws, necessitating long-term follow-up to confirm the initial findings of the study